Managing materiality: a preliminary examination of the adoption of the new GRI G4 guidelines on materiality within the business community. Issue 3 (30th September 2015) - Jones, Peter; Comfort, Daphne; Hillier, David
Abstract : The concept of materiality emerged as the most important element in the new G4 guideline on corporate sustainability reporting launched by the Global Reporting Initiative (GRI) in 2013. This commentary paper offers a preliminary examination of the way in which these new guidelines are being adopted within the business community. The paper begins with a short discussion of the GRI guidelines and the enhanced emphasis on materiality, and the paper draws its empirical material from the first 10 companies listed on Google as having published their sustainability reports in accordance with the G4 guidelines. The findings reveal marked variations in the ways, and the extent to which, the selected companies have initially adopted the GR4 guidelines on materiality and that many of the high‐priority material issues identified by these companies are centred on business continuity rather than environmental sustainability issues. Copyright © 2015 John Wiley & Sons, Ltd.